2007
DOI: 10.1177/0002716206294809
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Desegregation: Equal Opportunity Progress in U.S. Private Sector Workplaces since the Civil Rights Act

Abstract: Numerous commentators have concluded that the Civil Rights Act was effective in promoting increased access to quality jobs for racial minorities. Many have worried as well that the pace of change has been too slow or stalled, particularly after 1980. Few have directly discussed under what conditions we might expect equal employment opportunity (EEO) to flourish. Explanations of status inequalities in the workplace have primarily relied on theories of social conflict and discrimination. Organizational perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 45 publications
3
63
0
1
Order By: Relevance
“…On the one hand, because they are based on pairwise comparisons, they do not offer summary statistics of total segregation. On the other hand, they do not consider the wide range of races used here because most scholars have traditionally examined employment segregation between blacks and whites, only recently including Hispanics and/or Asians in their analyses (Mintz and Krymkowski 2011;Queneau 2009;Tomaskovic-Devey and Stainback 2007).…”
Section: Segregation By Race/ethnicitymentioning
confidence: 99%
“…On the one hand, because they are based on pairwise comparisons, they do not offer summary statistics of total segregation. On the other hand, they do not consider the wide range of races used here because most scholars have traditionally examined employment segregation between blacks and whites, only recently including Hispanics and/or Asians in their analyses (Mintz and Krymkowski 2011;Queneau 2009;Tomaskovic-Devey and Stainback 2007).…”
Section: Segregation By Race/ethnicitymentioning
confidence: 99%
“…We know that social processes associated with aging such as motherhood or tenure produce changes in wages (Budig & England 2001; Budig & Hodges 2010; Cotter et al 2004). Similarly, we know that period events like the passing of federal legislation can change employment and wage trajectories (Hirsch 2009; Leonard 1984, 1989; Tomaskovic-Devey & Stainback 2007). We also know that variations in the timing of life and labor market experiences such as entering the labor market during a recession can shift career trajectories for men and women (Kondo 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have even suggested that legal and legislative avenues are a productive means to narrowing the wage gap (Reskin 1988). It would be naïve to argue that equal employment legislation has eliminated gender discrimination from the workplace; however, evidence indicates that legal changes have had notable effects on occupational segregation and career trajectories (Hirsch 2009; Leonard 1984, 1989; Tomaskovic-Devey & Stainback 2007). Thus, legal changes offer strong theoretical motivation to expect period effects on the gender wage gap.…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman (2002), for example, found that almost one-third of black or white workers would have to change occupations to achieve full integration, while Reskin, McBrier, and Kmec (1999) noted that, proportionately, minorities were substantially underrepresented in over half the establishments studied by Kalleberg et al (1996). 1 Moreover, Tomaskovic-Devey et al (2006) and Tomaskovic-Devey and Stainback (2007) demonstrated that workplace desegregation for blacks and Hispanics in 2002 remained at 1980 levels.…”
mentioning
confidence: 99%